Quintendiskurse: Das Quintparallelenverbot in Quellentexten von 1330 bis heute - Saxer, Marion (Georg Olms Verlag, 2021)
The prohibition of fifth parallels is a counterpoint rule that every professional music student learns today. Less well known is the fact that the rule was first formulated as early as 1330 in the context of an oral practice of contrapuntal singing. Its historical emergence was not anchored in the cultural memory of European music. This volume fills this memory gap by presenting the almost seven-hundred-year history of the prohibition on the basis of sixteen source texts and detailed commentaries focussing on musicology, cultural studies and media studies. Among other things, this provides surprising insights into the listening and media history of European music.